Built to last: Theta and delta changes in resting‐state EEG activity after regulating emotions. Issue 6 (13th May 2022) - Lapomarda, Gaia; Valer, Stefania; Job, Remo; Grecucci, Alessandro
Abstract: Background: : Over the past years, electroencephalography (EEG) studies focused on task‐related activity to characterize cortical responses associated with emotion regulation (ER), without exploring the possibility that regulating emotions can leave a trace in the brain by affecting its oscillatory activity. Demonstrating whether the effect of regulation alters the brain activity after the session and whether this reflects an increased cognitive regulatory ability has great relevance. Methods: : To address this issue, 5 min of electrical brain activity at rest were recorded before and after (1) one session in which participants perceived and regulated (through distancing) their emotions (regulation session, ReS), and (2) another session in which they only perceived emotions (attend session, AtS). One hundred and sixty visual stimuli were presented, and subjective ratings of valence and arousal of stimuli were recorded. Results: : Behavioral results showed the efficacy of the regulation strategy in modulating both arousal and valence. A cluster‐based permutation test on EEG data at rest revealed a significant increase in theta and delta activity after the ReS compared to the AtS, suggesting that regulating emotions can alter brain activity after the session. Conclusions: : These results allowed us to outline a comprehensive view of the neurophysiological mechanisms associated with ER, as well as some possible implications in psychotherapy. Abstract : Graphical Abstract: